STABILITY INDICATING REVERSED PHASE-HIGH PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS DETERMINATION OF RELATED SUBSTANCES OF CITICOLINE AND PIRACETAM IN PHARMACEUTICAL DOSAGE FORM - Acharya, Manutosh; Ak, Jain; Garud, Navneet (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: A high-performance liquid chromatography (HPLC) method was developed and validated to determine stability indicating method of Piracetam and Citicoline in a tablet dosage. Methods: The separation was made using Inertsil C18, 250 × 4.6 mm, 5 µm column, mobile phase used contained phosphate buffer and acetonitrile in the gradient mode at wavelength of 205 nm for Piracetam and 280 nm for Citicoline on a PDA detector. Results: The method showed good linearity for, respectively related substances of Citicoline and Piracetam with correlation coefficients in the range of 0.29-623 µg/mL and 0.48-1030 µg/mL, respectively. Method accuracy was assessed at three levels; the recovery ranged between 100.0% and 102% for Citicoline and for Piracetam between 94.3% and 109.1%. Limit of detection and quantification for Citicoline was 0.07 µg/mL - 0.25 µg/ml and for Piracetam 0.12 µg/mL - 0.41 µg/ml. The solution was found to be stable within 27 hrs at room temperature. Conclusion: The method was demonstrated to be robust and simple, and suitable for industrial application for determination of related substances in the pharmaceutical preparation. Keywords: Piracetam, Citicoline, Assay, Reversed phase-high performance liquid chromatography.